Primary ectopic meningioma in the thoracic cavity: A rare case report and review of the literature - Liu, Xu; Liu, Jiao; Nai, Ting; Yang, Yuxia; Hu, Yuchang (Frontiers in Oncology, 2023)
Background Meningioma is a common type of intracranial tumor in adults. It rarely arises in the chest, with only a few case reports in the English literature. Here, we report the case of a patient with a primary ectopic meningioma (PEM) located in the thoracic cavity. Case presentation A 55-year-old woman presented with exercise-induced asthma, chest tightness, intermittent dry cough and fatigue for several months. Computed tomography revealed the presence of a huge mass in the thoracic cavity, with no connection to the spinal canal. Lung cancer and mesothelioma were suspected, and surgery was performed. Grossly, the mass was a grayish-white solid 9.5 cm × 8.4 cm × 5.3 cm in size. The microscopic morphology of the lesion was consistent with that of typical central nervous system meningioma. The pathological subtype was transitional meningioma. The tumor cells were arranged in a fascicular, whorled, storiform and meningithelial pattern, with occasional intranuclear pseudo-inclusions and psammoma bodies. In focal areas tumor cells were considerably dense, and the cells were round or irregular in shape, with less cytoplasm, uniform nuclear chromatin, and visible nucleoli and mitoses (2/10 HPF). By immunohistochemistry, the neoplastic cells showed strong and diffuse staining with vimentin, epithelial membrane antigen and SSTR2 with variable expression of PR, ALK and S100 protein. However, the cells were negative for GFAP, SOX-10, inhibin, CD34, STAT6, smooth muscle actin, desmin, CKpan, D2-40, WT-1, CK5/6 and CD45. The highest proliferation index by Ki-67 was 15%. The abnormal expression of ALK led to the initial misdiagnosis of an inflammatory myofibroblastic tumor. After 12 months of follow-up, no disease progression was observed. Conclusion The presence of primary ectopic meningiomas in the thoracic cavity is extremely rare, and this tumor is easily misdiagnosed clinically. Imaging is suggested to determine the location and possible differential diagnosis, while the final diagnosis should be via pathological examination. Immunohistochemistry is crucial for disease diagnosis. Owing to our limited knowledge of PEM, its pathogenesis and tissue of origin remain unclear. Clinicians should pay close attention to such potential patients. The present case report may provide insights into the diagnosis and therapy of patients with this tumor.